h² = side² - r²
h² = g² - m²
<>>
2006-12-26 14:23:25
·
answer #1
·
answered by aeiou 7
·
0⤊
0⤋
It is very straightforward. First you weigh the pyramid. Then you find the density of the pyramid using Archimedes's principle. From this, you can compute the volume of the pyramid. Then you find the area of the base of the pyramid. Since the volume V of the pyramid is 1/3 * h * A, where h is height and A is the area, the desired answer is simply 3V / A = h. Why anyone else doesn't see this is beyond me.
2006-12-26 22:45:13
·
answer #2
·
answered by Scythian1950 7
·
0⤊
0⤋
Depends upon whether the pyramid is oblique or a right pyramid where the altitude measure from the apex is perpendicular to the base of the pyramid at its center.
In the latter case, if you know the slant height and the distance from the center of the base to the point on the base where the foot of the slant height starts (call it a), then the height is
h= sqrt(s^2-a^2)
If you happen to know the Volume (V) and the area of the base (B), then h = V/B.
If the pyramid is oblique, then more info is required.
2006-12-26 22:50:05
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
I assume you are talking about a pyramid with a square base and equilateral triangles for sides.
Let
s = length of one edge of the pyramid
h = height of the pyramid
Given s, find h.
To visualize this, draw the two diagonals of the base. They will form a big X, and the intersection of the X is directly under the vertex of the pyramid. The distance from the intersection of the X to the vertex is the height of the pyramid.
d = length of the diagonal of the base
d = sâ2
The distance to the intersection of the X is have that or
d/2 = (sâ2)/2 = s/â2
Now we have three sides of a right triangle.
d/2
s = the length of an edge running from a corner of the base to the vertex
h² = s² - (d/2)² = s² - (s/â2)² = s² - ½s² = ½s²
h = s/â2
2006-12-27 01:19:42
·
answer #4
·
answered by Northstar 7
·
0⤊
0⤋
First find the length of the base of the pyramid
the formula to find the height is:
Tan of the angle = height divided by the 1/2 base
measure the angle to find the number of degrees between the base and the height of the pyramid. this will be the angle along the slope line from the end of the base and going to the top of the pyramid.
Look up the tangent of this angle in a set of tables or on a calculator.
so then a number such as .5039 for example is found
Note: this is a decimal number
then .5039 = height divided by half the base
therefore the height =tan x half the base
2006-12-26 23:33:49
·
answer #5
·
answered by David C 2
·
0⤊
0⤋
Use the pythagorean theorem.
If you know the lengths of 2 sides of a right triangle, it is possible to calculate the third side.
Imagine the pyramid a having been sliced diagonally from one corner to the opposite, exposing the surface of the interior of one side as being 2 identical "Right trianges"
Imagine the lengths around the bases of the pyramid as being line segments labelled AB,BC,CD, and DA. Imagine an segment AC that cuts from point A throught the solid pyramid to point C directly opposite.
You can calculate the line AC using this equation.
AB^2 + BC^2= AC^2
Say AB and BC are both 10 meters long.
10^2 + 10^2 = AC^2
100 + 100 = AC^2
200 = AC^2
AC = 14.14
NOw imagine another right triangle drawn from the top of the pyramid (point E) down to the middle of segment AC call that point F), back to A, and then along the line segment from A to E (AE)
AE^2 = AF^2 + FE^2
we can measure segment AE, lets presume it measures 15 meters. We know AF is equal to 1/2 of 14.14.. so....
15^2 = 7.07^2 + FE^2
225 = 49.48 +FE^2
225/49.48 = FE^2
4.50 = FE^2
FE= 2.12
In this hypothetical, the height of the pyramid is a shrimpy 2.12 meters.
2006-12-26 22:35:16
·
answer #6
·
answered by chocolahoma 7
·
0⤊
0⤋
a^2 + b^2 = c^2
(Diagonal length of base/2)^2 + height^2 = Outer Edge Length^2
Find the Diaognal length of the base (Corner of the base to oppisite corner of base) and divide it by two, then square it. Let that number be A.
Find the outer edge length (base corner to top) and square it. That's C. Subtract A from C (c - a), then the square root of the resulting number will be the height of the pyramid.
2006-12-26 22:24:29
·
answer #7
·
answered by socialdeevolution 4
·
0⤊
0⤋
by using its shadow n proportion. like at some point of the the day. ur height and the height of ur shadow is the same, measure the pyramid then n u will get its height.
2006-12-26 22:16:59
·
answer #8
·
answered by you 2
·
0⤊
0⤋
Pythagorean Theorem
c² = a² + b²
- - - - - - s-
2006-12-27 09:00:53
·
answer #9
·
answered by SAMUEL D 7
·
0⤊
0⤋